Penalaran dalam Putusan Mahkamah Konstitusi No. 64/PUU-X/2012 dalam kaitannya dengan Pelindungan Data Pribadi Nasabah Perbankan Di Indonesia - Iskandar, Yosea (UI Scholars Hub, 2023)
Abstract Title: The Significance of Constitutional Court Decision No. 64/PUU-X/2012 on Banking Customer Data Protection in Indonesia: An Analysis of Legal Interpretation and Implications This article delves into the pivotal role played by Constitutional Court Decision No. 64/PUU-X/2012 in shaping the concept and regulations governing the protection of personal banking data in Indonesia. The decision redefined the obligations of banks to maintain confidentiality, particularly concerning information about depositors and their deposits. Widely acclaimed as a legal breakthrough, the decision prompted the government to amend banking laws in 2022 to reflect the Court's new interpretation. In contrast to existing scholarly works on the subject, this analysis focuses primarily on the methods of interpretation and reasoning employed by the Supreme Court. The author argues that, without proper reasoning, even if a court decision aligns with societal needs at the time of its issuance, potential negative consequences must be anticipated. Conversely, accurate reasoning provides a deeper understanding of existing legal theories, valuable for future legal research. The article critically examines the legal innovation introduced by the Constitutional Court, categorizing it as a conditionally unconstitutional decision. The author questions the Court's authority to introduce new norms into legislation, exploring the historical and philosophical dimensions of this perspective. The implications of the decision are discussed, highlighting its self-executing and far-reaching character. Furthermore, the article scrutinizes logical fallacies present in the Court's reasoning. It identifies instances of post hoc fallacy, non sequitur, and hasty generalization, questioning the validity of conclusions drawn from certain premises. The Court's application of these fallacies, particularly in determining the constitutional infringement on spousal property rights, is dissected for inconsistencies and potential misinterpretations. The implications of Decision No. 64/PUU-X/2012 extend beyond the banking sector, influencing data protection regulations in various industries. The article emphasizes the need for further research to anticipate and address potential negative repercussions resulting from the broad impact of the Court's decision.